2019
DOI: 10.1021/acs.jnatprod.8b00918
|View full text |Cite
|
Sign up to set email alerts
|

Ascomylactams A–C, Cytotoxic 12- or 13-Membered-Ring Macrocyclic Alkaloids Isolated from the Mangrove Endophytic Fungus Didymella sp. CYSK-4, and Structure Revisions of Phomapyrrolidones A and C

Abstract: Three new 12- or 13-membered-ring macrocyclic alkaloids, named ascomylactams A–C (1–3), along with the analogues phomapyrrolidone C (4) and phomapyrrolidone A (5) were isolated from the mangrove endophytic fungus Didymella sp. CYSK-4. Their structures were elucidated by analysis of extensive spectroscopic data and mass spectrometric data. The structures and absolute configurations of 1 and 2 were determined by single-crystal X-ray diffraction experiments, which represents the first crystal structures described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 21 publications
(33 reference statements)
3
78
0
Order By: Relevance
“…AsA was prepared and purified from mangrove endophytic fungus Ascomycota sp. CYSK-4 as previously reported, and its structure was identified by interpretation of spectral data (MS, 1H NMR, 13C NMR, 2D NMR) and X-ray single crystal diffractive technique) [ 13 ]. The compound was dissolved in 99.9% dimethyl sulfoxide (DMSO) at a concentration of 10 mM as stock solution and diluted according to experimental requirements when used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…AsA was prepared and purified from mangrove endophytic fungus Ascomycota sp. CYSK-4 as previously reported, and its structure was identified by interpretation of spectral data (MS, 1H NMR, 13C NMR, 2D NMR) and X-ray single crystal diffractive technique) [ 13 ]. The compound was dissolved in 99.9% dimethyl sulfoxide (DMSO) at a concentration of 10 mM as stock solution and diluted according to experimental requirements when used.…”
Section: Methodsmentioning
confidence: 99%
“…AsA, as a decahydrofluorene analogue with a tetracyclic skeleton fused with a 13-membered macrocyclic moiety, is relatively rare in the decahydrofluorene class. We recently demonstrated that AsA can effectively suppress the growth of cell lines derived from a variety of human tissues, including MDA-MB-435, HepG2, HCT116, and NCI-H460 [ 13 ]. In the present study, we found that AsA could inhibit the proliferation of lung cancer cells and suppress tumor cell growth in xenograft mouse models without obvious toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Mangroves grow in the salt-tolerant ecosystems with high biodiversity, and the abundance and diversity of mangrove resources provide the great potential for the discovery of new compounds [22]. In recent years, multiple potential anticancer compounds have been found from mangrove-derived endophytic fungi [22][23][24][25]. In our previous study, we have isolated cytochalasin H (CyH) from endophytic fungus Phomopsis liquidambari derived from mangrove, which could induce apoptosis and inhibit migration and angiogenesis in NSCLC cells both in vitro and in vivo [26,27].…”
Section: Ivyspringmentioning
confidence: 99%
“…The systematic screening of marine microorganisms for the antibacterial activity revealed the strain of the Aspergillus genus [75], which produced sphingofungin I (239) and known polyketides including similar in structure sphingofungin D (240) [207]. Two new glycosilated alkylresorcins, resorcinosides A and |B (244,245), were isolated from the Penicillium janthinellum fungus [208]. Compounds 244 and 245 are the first representatives of the structural family of resorcinols, which are glycosylated at the alkyl, and not the aromatic, part of the molecule.…”
Section: Other Polyketidesmentioning
confidence: 99%
“…Three new macrocyclic alkaloids, ascomylactams А-С (308-310) were isolated from mangrove endophyte Didymella sp. CYSK-4 [244], along with the known analogs, phomapyrrolidones A and C (311, 312) [245], structure of which was refined. Two new stereoisomeric alkaloids, cladosporitins A (313) and B (314), were isolated from the culture fluid of the mangrove micromycete Cladosporium sp.…”
Section: Alkaloidsmentioning
confidence: 99%